Design and Development of a Pipeline Maintenance System for Pipe Surge and Water Hammer Equipment Based on Siemens S7-1200 PLC - Wirandi, Mohammad; Saputra, Deni; Supardi, Supardi (Jurnal Teknologi dan Manajemen, 2024)
Fluids play a crucial role in the lives of living beings, as they are substances that can flow. In a piping system, a common issue is water pressure fluctuation caused by sudden closures of water flow (Idul, 2021). Pipe surge and water hammer equipment are utilized to demonstrate the transient pressure effect resulting from abrupt changes in flow velocity within pipes (David, 1981). Water hammer can lead to pressure surges throughout the piping system, potentially causing failures that result in leaks in pipes, valves, pipe joints, and even pumps if the pressure exceeds the pipe's capacity (Prasetya, 2016). The likelihood of pipe ruptures or leaks at joints increases significantly. Additionally, equipment movement, slope, and precision of pipe installation can also contribute to leaks during water hammer events. This research aims to develop a pipe leakage monitoring system to address the impact of water hammer. The system will be installed in areas deemed susceptible to this phenomenon, along with a periodic maintenance indicator system to minimize the impact of pipe leaks. The research will also investigate the potential risks associated with varying fluid flow rates in the piping system. The monitoring, indicator, and sensor systems will be integrated into a PLC and HMI system for data processing.